The diagnostic and prognostic value of angiopoietins compared with C-reactive protein and procalcitonin in children with febrile neutropenia - Esra Mimaroğlu; Elvan Çağlar Çıtak; Necdet Kuyucu; Gülçin Eskendari (The Turkish Journal of Pediatrics)
In this study, we aimed to determine serum angiopoetin (Ang) levels and compare them with levels of C-reactive protein (CRP) and procalcitonin (PCT). Cancer patients (aged 0-18 years) who experienced febrile neutropenia attacks were included in the study. Ang-1, Ang-2, CRP, and PCT were analyzed at admission and 2nd day. Ninety-four episodes of febrile neutropenia that developed in 62 patients were analyzed in this study. The mean age of the patients was 7.56 ± 4.8 (0.5-17) years. The patients had lymphoma (33.9%), solid tumors (48.4%), and other cancer (17.7%). The percentages of the patients with fever of unknown origin (FUO), clinically documented infection (CDI), and microbiologically documented infection (MDI) categories were 45.7%, 22.3%, and 31.9%, respectively. During the study period 11 patients were lost to follow-up. The levels of CRP, PCT and Ang-2 were significantly higher; and that of Ang-1 was significantly lower, compared to the controls. The differentiation cannot be made between the groups by CRP and PCT levels. The level of Ang-1 was the lowest in MDI group; the level of Ang-2 and the ratio of Ang-2/Ang-1 were high in each group. Ang-1, Ang-2 and the ratio of Ang-2/Ang-1 were significantly associated with mortality. Angs correlated with the severity of infection.